2020
DOI: 10.1590/1678-992x-2018-0349
|View full text |Cite
|
Sign up to set email alerts
|

Repeated geophysical measurements in dry and wet soil conditions to describe soil water content variability

Abstract: There is an increasing interest in the application of geophysical surveys to assess the soil water content (SWC) variation in both spatial and temporal scales. In this work, a geophysical survey was carried out at an experimental farm in dry and wet conditions. We determined the SWC data measured with the gravimetric method, apparent electrical conductivity by electromagnetic induction (EMI) and amplitude of Ground Penetrating Radar (GPR) data at different frequencies. Geophysical sensors are an efficient tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This result suggested that the variability of the moisture content did not significantly influence the variability of the ECa and, probably, the correlation could be the highest with other soil properties. Therefore, although previous studies refer to the influence of soil moisture on electrical conductivity [47][48][49], the findings of this research indicated limitations for the use of EMI sensors as an indicator of SWC and that one sensor alone cannot achieve a good estimation of soil spatial variation [41,42]. Since both the surface topography and the soil discontinuities play an important role in influencing spatial ECa variation [50], the radargram analysis and interpretation might help to identify soil discontinuities and their depths.…”
Section: Swc and Eca Mapsmentioning
confidence: 71%
See 1 more Smart Citation
“…This result suggested that the variability of the moisture content did not significantly influence the variability of the ECa and, probably, the correlation could be the highest with other soil properties. Therefore, although previous studies refer to the influence of soil moisture on electrical conductivity [47][48][49], the findings of this research indicated limitations for the use of EMI sensors as an indicator of SWC and that one sensor alone cannot achieve a good estimation of soil spatial variation [41,42]. Since both the surface topography and the soil discontinuities play an important role in influencing spatial ECa variation [50], the radargram analysis and interpretation might help to identify soil discontinuities and their depths.…”
Section: Swc and Eca Mapsmentioning
confidence: 71%
“…However, since the spatial patterns of SWC could have been influenced by the variations in soil depth and soil/bedrock interface [40], the combination of different sensors and integrating their data could discriminate whether or not agronomical factors (hydraulic arrangement, organic amendment application, etc.) can modify SWC distribution [41], and could also provide its more accurate…”
Section: Swc and Eca Mapsmentioning
confidence: 99%
“…The maximum depth of these ponds is approximately 1.6 m (Figure Ground Penetrating Radar (GPR) and Electromagnetic Induction (EMI) can be tremely valuable for the collection of spatial data that correlate with the soil types Ground Penetrating Radar (GPR) and Electromagnetic Induction (EMI) can be extremely valuable for the collection of spatial data that correlate with the soil types and Ground Penetrating Radar (GPR) and Electromagnetic Induction (EMI) can be extremely valuable for the collection of spatial data that correlate with the soil types and hydrological properties of a terrain (e.g., [88][89][90][91][92]). The geophysical survey techniques employed in the present study have also been used to successfully investigate the physical properties of the soil and subsoil in research in scientific fields such as agronomy, archeology, hydrology, and wetland ecology (e.g., [23,37,88,[93][94][95][96][97][98][99][100][101][102][103][104][105][106]). References [22,107] predicted that the integration of geophysical tools (e.g., Electrical Resistivity Tomography (ERT), EMI, and GPR) with remote sensing will contribute to the successful development of precision agriculture.…”
Section: Discussionmentioning
confidence: 99%